THE ROLE OF SOCIAL MEDIA IN THE ETHNIC REJECTION MOVEMENT ROHINGYA - Nurfazillah; Fasya, Teuku Kemal; Nasution, Pangeran Putra Perkasa Alam; Maliati, Nulwita; Sari, Dewi Kumala (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2025)
This study examines the role of social media in the Rohingya ethnic rejection movement (On social media from November 2023 - January 2024). The study discusses how this social media leads public opinion so that people reject the presence of the Rohingya ethnic group in Aceh. The focus of the problem in this study is how social media as a tool can shape narratives and disseminate information that influences public opinion towards the rejection of the Rohingya ethnic group. This study uses Framing Theory by Erving Goffman which explains how the media constructs and frames an issue. The research method used in this study is a qualitative research method. The results obtained from this study are that social media has become a barometer for the public to see and assess the situation that occurs, one of which is the arrival of the Rohingya ethnic group in Aceh. Social media also plays an important role in strengthening narratives and disseminating information that influences public opinion towards the Rohingya. The rejection movement is a form of resistance carried out by the Acehnese people against the presence of the Rohingya ethnic group. Rejection of Rohingya refugees in Aceh is a response from the community who feel threatened by their arrival and consider that local rights and interests must be prioritized.